PENINGKATAN HASIL PEMBELAJARAN TEMATIK DENGAN MENGGUNAKAN INKUIRI DI SEKOLAH DASAR - Achni Zahara; Yuliar M; Reinita Reinita (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research is motivated by thematic learning which so far the teacher in teaching thematic learning is still separated by subject so that less effective thematic learning takes place. Besides that the standard of completeness in the desired thematic learning has not been achieved. The purpose of this study is to improve the learning process of mathematics using the inquiry approach for class II SDN 35 Kuranji. The approach used is a qualitative and quantitative approach. This research data is in the form of information about the process and data on the results of actions obtained from the results of attitude assessment, knowledge assessment, skills assessment. The data source is the process and results of the implementation of thematic learning using the inquiry approach in class II SDN 35 Kuranji. The results of the study increasedobservation of RPP inthe firstcyclwas 82.95%, in the second cycle 83.90% and in the third cycle 90.90%. The teacher aspect of the first cycle was 80.35%, the second cycle 92.25% to 92.85% in the second cycle and in the aspects of the student cycle I was 80.35% to the first cycle to 92.85% in the third cycle. So, the inquiry approach can improve the integrated thematic learning process.Key terms: integrated thematic learning, inquiry approach